In vitro antiproliferative activity of palladium(ii) thiosemicarbazone complexes and the corresponding functionalized chitosan coated magnetite nanoparticles - Hernández, Wilfredo (2016)
W. H. thanks Universidad de Lima Scientific Research institute for financial support. E. S., M. T., M.A. and J.M. thank Basal Project FB0807 (CEDENNA), and Y.E. thanks FONDECYT Project 3130418.